Pyroptosis Regulators and Tumor Microenvironment Infiltration Characterization in Clear Cell Renal Cell Carcinoma - Zhang, Xi; Wei, Xiyi; Wang, Yichun; Wang, Shuai; Ji, Chengjian; Yao, Liangyu; Song, Ninghong (Frontiers in Oncology, 2022)
Background: It was well known that chronic inflammation can promote the occurrence and progression of cancer. As a type of pro-inflammatory death, pyroptosis can recast a suitable micro-environment to promote tumor growth. However, the potential role of pyroptosis in clear cell renal cell carcinoma (ccRCC) remained unclear. Methods: The transcriptome expression profile and mutation profile data of ccRCC with clinical characteristics included in this study were obtained from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases. Consensus Clustering was used for clustering. Single sample gene set enrichment analysis (ssGSEA) and gene set enrichment analysis (GSEA) analysis were applied to evaluate pathways. CIBERSORT, EPIC algorithm, and Tumor Immune Estimation Resource (TIMER, http://timer.cistrome.org/) were applied for evaluating the proportion of various immune infiltrating cells across diverse cancer types. ESTIMATE algorithm was involved to compute the immune micro-environment scores. Results: Among the 17 pyroptosis regulators, a total of 15 pyroptosis regulators were differential expressed between tumor and normal tissues, in which 12 of them emerged strong correlations with prognoses. According to the pyroptosis components, the ccRCC patients were divided into four pyroptosis subtypes with different clinical, molecular, and pathway characteristics. Compared with other subtypes, cluster B showed the pyroptosis heat phenotype, while cluster D represented the pyroptosis cold populations with poor overall survival. In addition, we performed principal component analysis (PCA) on the differential genes between the clusters to construct the pyroptosis index. Furthermore, the pyroptosis index was significantly correlated with survival in different tumor mutation statuses and different grades&stages. Besides, the expression of pyroptosis related genes was related to the infiltration of immune cells and the expression of immune checkpoints, among which AIM2 was considered as the most significant immune-related pyroptosis regulator. Ultimately, we found that AIM2 was related to the immune activation pathway and was significantly overexpressed in tumor tissues. Conclusion: This study revealed that pyroptosis regulators and pyroptosis index played an important role in the development and of ccRCC. Moreover, AIM2 can be used as a predictor of the response of immunotherapy. To assess the pyroptosis patterns may help evaluate the tumor status and guide immunotherapy strategies.